Conceptualization and Measurement of Trust in Home–School Contexts: A Scoping Review - Shayo, Happy Joseph; Rao, Congman; Kakupa, Paul (Frontiers in Psychology, 2021)
Objective and method: This review unravels the complexity of trust in home-school contexts across the globe by drawing on 79 peer-reviewed quantitative empirical studies spanning over two decades (2000-2020). The goal is to refocus attention on how trust has been defined and operationalized in recent scholarship. Findings: The findings reveal four essential pillars in the conceptualization of trust: the trustor’s propensity to trust, shared goals, the trustor-trustee relationship, and the trustee’s trustworthiness. However, the operationalization of trust in existing measures does not fully capture these essential pillars, as it is mainly based on trustee characteristics of benevolence, reliability, openness, competence, and honesty rather than on the trustor’s actual trust behavior. Conclusion: Most ‘trust studies’ essentially measuring trustworthiness and not the purported trust. Therefore, a shift in the conceptualization and measurement of trust is proposed. The review contributes to the understanding and assessment of home-school and workplace relationships.